Patient satisfaction with services at the Family Medicine Employee Clinic in a tertiary hospital in Riyadh - Allafi, Abrar H. (J Family Med Prim Care, 2021)
BACKGROUND: Patient satisfaction reflects the healthcare quality of the facility. Therefore, it is important to determine satisfaction level of the patient satisfaction in order to improve services'quality provided to patients. AIM: to assess the satisfaction level of patients at the Family Medicine Employee Clinic at a tertiary hospital in Riyadh, Saudi Arabia. This study is a cross-sectional that included 224 patients. METHOD: The study was conducted in King Fahad Medical City at the Family Medicine Employee Clinic between March and December 2019. Self-administered questionnaires were used to gather the data. The questionnaire included questions regarding the demographics of patients and questions to examine their satisfaction with the services provided by the clinic. SPSS version 21 was used for data analysis. RESULTS: The study comprised 90 patients, 71.1% of which were female; 77.8% of participants lived in Riyadh; 92.2% of patients were in the age range of 25–75 years; 51.1% were single; 56.7% had income lower than 10,000 SR; 63.3% had college education; and 95.6% were employees of King Fahd Hospital. The mean ± SD of satisfaction was determined to be at 8.6 ± 1.7. There was a significant inverse correlation between income and satisfaction (P = 0.03). CONCLUSION: Patients reportedly showed high levels of satisfaction, especially regarding the experience of nurses, ease of registration and making appointments, treatment by receptionists, and cleanliness of clinics. The results of the survey reflect the effectiveness and efforts of the employees of the clinic.